The Influence of Islamic Financial Institutions in the Sustainable Development Goals Agenda in Indonesia - Hasibuan, Ahmad Fauzul Hakim; Nur, Mukhlis M.; Cheren, Yola Deviani (Journal of International Conference Proceedings, 2023)
This study aimed to analyze the influence of the financing of Islamic Financial Institutions, namely slamic Microfinance Institutions, Sharia Financing Companies, Sharia Pawnshops, and Sharia Venture Capital on the SDGs Agenda in Indonesia from 2017 to 2022. This study used secondary data, and the data analysis method used was panel data regression analysis using the Random Effect Model with the help of Eviews 10. The results of this study indicated that poverty in Indonesia can be explained by Islamic Microfinance Institutions, Sharia Financing Companies, Sharia Pawnshops, and Sharia Venture Capital by 18.91% (R2). Then the regression coefficient showed that (1) financing from Islamic Microfinance Institutions did not have a significant effect on the 5% real level with a probability value of 0.8734 and was negatively related to the coefficient value obtained of 0.018714, (2) Financing from Islamic finance companies did not have a significant effect at the 5% real level with a probability value of 0.8956 and positively related to the coefficient value obtained of 0.018269, (3) Sharia pawnshop financing had no significant effect at the 5% real level with a probability value of 0.9348 and wasÂ  negatively related to the coefficient value obtained at 0.025233, (4) The variable ofÂ  Sharia Venture Capital financing had no effect at the 5% real level with a probability value of 0.9854 and was negatively related to the coefficient value obtained of 0.000151. Furthermore, poverty in Indonesia was significantly influenced by these variables at 10.85% (F-Statistic).